1988
DOI: 10.2136/sssaj1988.03615995005200030010x
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Characteristics of Organic Compounds on hexadecyltrimethylammonium‐Smectite

Abstract: When hexadedyltrimethylammonium (HDTMA) ion is exchanged for metal cations like calcium in smectite, the sorptive properties of the clay are greatly modified. The resultant HDTMA‐smectite complex behaves as a dual sorbent, in the sorption of organic compounds, in which the mineral fraction functions as a solid adsorbent and the organic (HDTMA) phase as a partition medium. Capacities of mineral adsorption and partition uptake by HDTMA in the HDTMA‐smectites are illustrated by sorption of benzene, trichloroethen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
295
0
10

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(315 citation statements)
references
References 0 publications
10
295
0
10
Order By: Relevance
“…In this way, the organophobic interlayer space of montmorillonite clay minerals are converted to organophilic one. By contrast with the pristine montmorillonite, the resultant OMMT materials display a much higher rate and capacity in the adsorption of organic ions and molecules [11,12]. Hence, so far OMMT materials as a class of adsorbents have been widely tested in the removal of organic pollutants from wastewater [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the organophobic interlayer space of montmorillonite clay minerals are converted to organophilic one. By contrast with the pristine montmorillonite, the resultant OMMT materials display a much higher rate and capacity in the adsorption of organic ions and molecules [11,12]. Hence, so far OMMT materials as a class of adsorbents have been widely tested in the removal of organic pollutants from wastewater [13].…”
Section: Introductionmentioning
confidence: 99%
“…Organo montmorillonites (OMts) have found wide applications in organic pollution control fields because of their excellent adsorption capacity towards hydrophobic organic compounds (HOCs) [1][2][3][4][5][6]. Understanding microstructure of this kind of organoclays is of high importance for clarifying their adsorption characteristics and improving their adsorption efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The structural characteristics, such as basal spacing, surface area, porous structure and arrangement models of organic cations, have been reported in numerous publications [7][8][9][10][11][12][13][14][15][16]. Based on the obtained structural information, the potential correlation between microstructure and adsorption characteristics of organoclays has been proposed in several reports [1,[17][18][19][20][21][22]. Chen et al [5] indicated that as the arrangement model of organic cations evolves from flat-monolayer to flat-bilayer, to pseudo-trilayer, then to paraffin-monolayer and finally to paraffin-bilayer with the increase of their loading amounts, the alkyl chains will first form strong adsorbed organic film and then gradually transfer to weak partition organic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Various organoammonium exchanged montmorillonites have been synthesized, and the properties and applications have been investigated as so-called "organopbilic clays" which swell in organic solvents to form a thixotropic gel (Jordan, 1950;Jones, 1983). These organoammonium-clays have been studied as a chromatographic stationary phase (Bondarenko et al, 1982), shape selective adsorbates (Barrer, 1978), sorbents for organic contaminants dissolved in water (Lee et al, 1989(Lee et al, , 1990Boyd et al, 1988aBoyd et al, , 1988bJaynes et al, 1991), catalysts (Cornelis and Laszlo, 1982), rheology controlling agents in a wide variety of solvent systems (Jones, 1983), and so on. The modifications have provided new ways to utilize swelling clay minerals in practice.…”
Section: Introductionmentioning
confidence: 99%